Designing with Aluminium: Aluminium in the Architecture of 1970s Ankara - Funda Uz (LookUs Bilisim A.S., 2019)
In Turkey, “modern architecture” has frequently been investigated and discussed through ideological dimension and its morphological representation. However, when compared with international studies, research about the effects of building materials on modern architecture is insufficient within the scope of Turkey. This article aims to produce the unique tools of reading the structures which were generated and were kept alive by people, by production mechanisms, by conditions of period and by relations of context. In chronology-oriented studies, between Post-war Modernism and 1950-1980 era, it was aimed to read the architectural production in the 1970s -whose distinctiveness has not been emphasized adequately- through aluminum as a building material within the frame of production, criticism, and culture. After the 1950s with the original and precessor examples of 1960s; as the scope of this study, 1970s can be considered as the beginning of standardization and acceleration of industrialization. Ankara, the case city of this study, indicates a threshold within the history of the construction of Turkey in the aforementioned period. Urban development of Ankara, increase of population and labor force, respond to the building needs of bureaucratic institutions with their newly-established units verify the definition of “Architecture of Ankara”. It is a common and accepted judgment to describe the architecture produced between 1960-1980 in Ankara as “international” and “modern”. The potential of creating extensions is clearly seen, for widening our knowledge about the built environment in this period through deepening research on the morphological and functional conditions, the needs to them, the space-politics which creates them, included actants and institutions.
Keywords: aluminum designs; post-war modernism; Urbanization. City and country; ankara; architectural aluminum; s architecture; HT361-384